Exploring Experiences of Science Education Teachers on Professional Development (Orchid Academia Siraha, 2023)
Maintaining current pedagogical strategies and remaining cutting-edge with regular updates is crucial in the field of science education, where professional development is a foundation for developing effective teaching and learning. In an effort to pinpoint issues and provide solutions, this study explores the condition of professional development among science education teachers at the Faculty of Education, Tribhuvan University (TU-FOE), Nepal. The study uses a qualitative research design that includes in-depth interviews and document analysis to provide knowledge of the professional development genre. The study's findings shed light on the complications faced by science education teachers, such as a lack of resources and support, institutional policies, technological barriers, professional burnout and a lack of opportunities for collaboration. These challenges highlight the potential link between the need for creative, specialized professional development opportunities that meet the changing demands of the sector and the requirements for science education. Therefore, the TU-FOE authority minimizing these issues and launching the professional development programme  for enhancing the quality of science education teachers to improve the quality of teaching and learning in the Faculty of Education, Tribhuvan University.